2022
DOI: 10.1186/s12890-022-02018-7
|View full text |Cite
|
Sign up to set email alerts
|

MMP2 and MMP9 contribute to lung ischemia–reperfusion injury via promoting pyroptosis in mice

Abstract: Background Lung ischemia–reperfusion injury (LIRI) is a cause of poor prognosis in several lung diseases and after lung transplantation. In LIRI, matrix metalloproteinases and pyroptosis indicators change in parallel, both of them involvement of inflammatory modulation, but it is unclear whether they are related to each other. Methods We analyzed the matrix metalloproteinases (MMPs) changes from RNA sequencing (RNA-Seq) data of human transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…63 In addition, increased activity of Caspase-1 and IL-1β were observed after IRI, and the lung pyroptosis and injury alleviated when treatment the mice with MMP9 selective inhibitor SB-3CT, suggesting MMP9 involvement in IRI after lung transplant, potentially associated with promoting lung pyroptosis. 64 The transcriptome analysis in this study showed elevated MMP9 mRNA levels after reperfusion, and we observed a significant difference in MMP9 plasma levels between pre-and post-transplant of total 24 lung transplant patients. Nonetheless, no significant peri-reperfusion differences were observed in patients with PGD 2 grade or above, possibly due to the limited sample volume.…”
supporting
confidence: 52%
“…63 In addition, increased activity of Caspase-1 and IL-1β were observed after IRI, and the lung pyroptosis and injury alleviated when treatment the mice with MMP9 selective inhibitor SB-3CT, suggesting MMP9 involvement in IRI after lung transplant, potentially associated with promoting lung pyroptosis. 64 The transcriptome analysis in this study showed elevated MMP9 mRNA levels after reperfusion, and we observed a significant difference in MMP9 plasma levels between pre-and post-transplant of total 24 lung transplant patients. Nonetheless, no significant peri-reperfusion differences were observed in patients with PGD 2 grade or above, possibly due to the limited sample volume.…”
supporting
confidence: 52%
“…In the respiratory organ, pretreatment with recombinant high-mobility group box 1 protein (rHMGB1) inhibited pyroptosis of alveolar macrophages through the Keap1/Nrf2/HO-1 signaling pathway, thus fighting against lung I/R injury [ 114 ]. In addition, it has been suggested that matrix metallopeptidase 2 (MMP2) and matrix metallopeptidase 9 (MMP9) contribute to lung I/R injury via the promotion of lung pyroptosis [ 115 ]. In summary, all the above results provide new insights into inhibiting pyroptosis in the treatment of I/R injury in these organs.…”
Section: Pyroptosis and I/r Injurymentioning
confidence: 99%
“…This promising laboratory finding suggests that disulfiram could be a potential pharmacological tool to provide more insights in the context of pyroptosis and its role in organ transplantation. Although pyroptosis has not been extensively studied in the context of organ transplantation, a growing body of experimental evidence implicates its involvement in various IRI models of transplantable solid organs [ 93 97 ]. Collectively, the preclinical and clinical findings suggest that inhibition of pyroptotic pathway could provide effective and innovative therapeutic approach to attenuate IRI and its associated complications after organ transplantation.…”
Section: Cell Death In Ischemia–reperfusion Injurymentioning
confidence: 99%